Women’s Spiritual Agency in Marriage: Enhancing Husbands’ Religiosity in Contemporary Contexts - Sufrin Efendi Lubis; Riem Malini Pane; Cecep Soleh Kurniawan (MAN 4 Kota Pekanbaru, 2025)
This study examines the role of wives in enhancing their husbands’ religiosity in modern Muslim families, particularly in Padangsidimpuan City. Viewing the family as a spiritual institution, the research explores how religious values are cultivated through daily interaction, exemplary conduct, and meaningful communication. Using a descriptive qualitative approach, it draws on a literature review and in-depth interviews with five Muslim married couples, analyzed thematically to reveal patterns of the wife’s spiritual influence. The findings show that a wife’s devotion in worship, moral behavior, and positive religious communication significantly strengthen her husband’s religiosity. Her exemplary conduct and empathetic communication create a religious atmosphere that nurtures spiritual awareness at home. Modern wives who balance domestic and professional roles also contribute to the family’s spiritual resilience. Thus, the wife’s role embodies dakwah bil hal, serving as a spiritual catalyst who inspires her husband’s piety and supports a harmonious, faith-centered family.